2001
DOI: 10.1080/00480169.2001.36206
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintics for the control of nematode infections in the brushtail possum (Trichosurus vulpecula)

Abstract: The doses of anthelmintics required to effectively control nematodes in possums were higher than those recommended for animals for which they are currently registered. Possums tolerate the high dose rates of anthelmintics used in this study without apparent adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This is partially demonstrated by our results, where double-dose moxidectin produced a greater decline in FECs than did the other two treatments. In a study of the efficacy of anthelmintics in another marsupial, the common brushtail possum (Trichosurus vulpecula), Ralston et al (2001) found that 5-7 times the manufacturer's recommended dose of various anthelmintics was required to effectively control nematodes (Parastrongyloides trichosuri and Paraustrostrongylus trichosuri).…”
Section: Discussionmentioning
confidence: 99%
“…This is partially demonstrated by our results, where double-dose moxidectin produced a greater decline in FECs than did the other two treatments. In a study of the efficacy of anthelmintics in another marsupial, the common brushtail possum (Trichosurus vulpecula), Ralston et al (2001) found that 5-7 times the manufacturer's recommended dose of various anthelmintics was required to effectively control nematodes (Parastrongyloides trichosuri and Paraustrostrongylus trichosuri).…”
Section: Discussionmentioning
confidence: 99%